(De) Escalatory Framing Analysis of Photographs of Terrorist Organisation in the Press of Pakistan - Ahmad, Raza Waqas; Dr. Rooh Ul Amin Khan,; Dr. Zafar Iqbal, (Journal of Peace, Development and Communication, 2025)
This research focuses on analysing the representation of the Taliban conflict in four popular Pakistani dailies: Nawa-i-Waqat, Express, The News, and Dawn during three different regimes of Pakistan’s government from 2004 to 2015. The research is concerned with the analysis of escalatory and de-escalatory images to examine the patterns of media reports on the events at different phases of the conflict. The observation confirms that with references to intensity of the war, there is more conflicts reflected in photographs identified. High tension symbolic pictures of the conflict accompanied with violent images were most commonly used, stressing the role of media in presenting the conflict merely as the act of violence. Positive peace messaging or what I refer to here as de-escalatory photos, largely encompassing effort to denote phases of war, were noted frequently during the containment and agreement phases though tremendously reduced during phases of escalation. This implies a change of editorial policies and possibly a change of tack in how media handles the reporting of conflict. There are also observations regarding newspaper’s preference – Express prefers more of strong escalatory photos while Dawn is moderate. Indeed, it was possible to observe only miniscule shifts in the application of the general principles of peace journalism that are supposed to offer a more balanced perspective of the conflict. It therefore supports the notion the media plays an important role in informing the public on conflict. The type of images the media specialising in the conflict with the Taliban used in its outputs shifted with time and primarily focused on escalation because of the changes in the editors’ concerns and audience interests.